Evidence for the development of oceanic crust and for continental rifting in the tectonostratigraphy of the Early Proterozoic Cape Smith Belt - St-Onge, M.; Lucas, S.; Scott, D.; Begin, N. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1989)
Summary The Cape Smith Belt contains evidence forearly Proterozoic plate tectonics in the form of a 1998 Ma ophiolite and a thrust belt which developed during northward under thrustingof a continental rift margin. Five tectono stratigraphic suites have been recognized from north to south in the eastern portion of the belt: (l) fluviodeltaic sediments; (2) ca. 1960Ma sediments and continental tholeiiticbasalts; (3) ca. 1920 Ma transitional crustbasalts; (4) deep-water sediments; and (5) basalts, sheeted dykes and mafic and ultra-mafic cumulates of a 1998 Ma ophiolite.Suites (1 ) to (3) reflect the development of a north-facing rift margin at the edge of the Superior Province. The older age of theophiolite suggests that it developed in an earlier-rifted segment of the same basin, orit formed in a separate basin independent of the rift margin.